Lean Management dalam Perspektif Filsafat Ilmu Manajemen: Kajian Epistemologis - Siti Muthmainnah; Agus Suradika (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This article examines Lean Management from the perspective of the philosophy of management science, focusing on its epistemological foundations. Lean Management has been widely implemented as an efficiency-oriented managerial approach, yet its scientific and philosophical basis is rarely discussed. This study aims to explain how Lean Management knowledge is constructed, validated, and developed within management science. Using a qualitative literature review complemented by quantitative research tendencies, the study reveals that Lean Management is grounded in positivist and pragmatic epistemology, while also requiring interpretive understanding in organizational practice. The findings position Lean Management as an applied scientific paradigm rather than merely a technical toolkit.